ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 1 ULUSUSUA PADA MATERI KOORDINAT KARTESIUS - Mesrawati Ndruru (Afore : Jurnal Pendidikan Matematika, 2024)
The problem of this research is the lack of ability to understand mathematical concepts of class VIII students at SMP Negeri 1 Ulususua on Cartesian Coordinates material. The aim of this research is 1) To describe the ability to understand mathematical concepts of class VIII students at SMP Negeri 1 Ulususua on Cartesian coordinates material through a test of the ability to understand mathematical concepts. 2) to find out students' obstacles in completing Cartesian coordinates material through a test of the ability to understand mathematical concepts. This type of research is qualitative research with a descriptive approach. The informants in this research were 22 students in class VIII of SMP Negeri 1 Ulususua. Based on the results of tests on the ability to understand mathematical concepts of class VIII students at SMP Negeri 1 Ulususua on Cartesian coordinates material, it is known that the average student score is 45.55, which can be classified into several score categories, namely 1 person (5%) has a very good score, 2 good scores. people (9%), the fair score was 10 people (45%), the poor score category was 7 people (32%) and the very poor score was 2 people (9%). So it can be concluded that the ability to understand mathematical concepts of class VIII students at SMP Negeri 1 Ulususua is dominant in the sufficient score category. The obstacles faced by students in completing the test are that students are less able to understand the concept of material and classify the concept of Cartesian coordinates in the questions, students are less able to develop their thinking regarding the concept of Cartesian coordinates, students do not understand the representation of the concept of Cartesian coordinates and students are less able to use algorithms. solve the problem correctly. Researchers suggest that students must understand the importance of the ability to understand mathematical concepts and teachers should pay attention to how important students' ability to understand mathematical concepts is in mathematics learning.